Modeling Developmental Brain Diseases Using Human Pluripotent Stem Cells-Derived Brain Organoids – Progress and Perspective. Issue 3 (15th February 2022) - Bhattacharya, Afrin; Choi, Wendy W.Y.; Muffat, Julien; Li, Yun
Graphical abstract: Highlights: Brain organoids have been used to model a number of developmental brain disorders. Brain organoid models have provided new insights into disease etiology. Ongoing and future improvement will facilitate further application. Abstract: Developmental brain diseases encompass a group of conditions resulting from genetic or environmental perturbations during early development. Despite the increased research attention in recent years following recognition of the prevalence of these diseases, there is still a significant lack of knowledge of their etiology and treatment options. The genetic and clinical heterogeneity of these diseases, in addition to the limitations of experimental animal models, contribute to this difficulty. In this regard, the advent of brain organoid technology has provided a new means to study the cause and progression of developmental brain diseases in vitro . Derived from human pluripotent stem cells, brain organoids have been shown to recapitulate key developmental milestones of the early human brain. Combined with technological advancements in genome editing, tissue engineering, electrophysiology, and multi-omics analysis, brain organoids have expanded the frontiers of human neurobiology, providing valuable insight into the cellular and molecular mechanisms of normal and pathological brain development. This review will summarize the current progress of applying brain organoids to model human developmental brain diseases and discuss the challenges that need to be overcome to further advance their utility.